Enhancing community engagement initiatives through moderate communitarianism - Zayd Waghid (Discover Education)
Abstract Community engagement initiatives, which include ideas of social change and collaboration, seek to value and use students’ knowledge in real-world situations. However, a lack of connection between academic learning and the community environment may result in disengagement on the part of students. The article argues that, by including the philosophy and practice of moderate communitarianism in CEI, it is possible to balance individual rights with community obligations, in this way bridging the existing divide between the two. Based on Kwame Gyekye’s thoughts, this article presents a conceptual framework that highlights the importance of humanity in the African sense (Ubuntu), interdependence, communalism, and respect and dignity concerning CEI. I argue that these four aspects have the potential to provide a harmonious relationship between individual autonomy and society's requirements and, in so doing, to improve educational outcomes and, in turn, the advancement of social equality.